Albania : Request for Purchase under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Albania. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper focuses on Albania's Request for Purchase Under the Rapid Financing Instrument (RFI). The RFI provides rapid financial assistance to member countries facing an urgent balance of payments need, without the need for a full-fledged economic program or reviews. A sizeable increase in the fiscal deficit of 2020 is necessary to limit the impact of coronavirus disease 2019 (COVID-19). It will be critical to ensure adequate spending for healthcare and support for the people and firms that are hurt by the COVID-19 pandemic. The Albanian authorities remain committed to ensuring macroeconomic stability. Once the shocks have been overcome, it will be important to keep public debt on a clear downward path. The IMF staff supports the authorities' request for financial assistance under the RFI to address the urgent balance of payments need due to exogenous shocks related to the 2019 earthquake and the COVID-19 pandemic. The balance of payments financing need is expected to be temporary.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet